Sistem Layanan Informasi Mahasiswa Universitas Atma Jaya Makassar Berbasis Email - Sean Coonery Sumarta; Astrid Lestari Tungadi; Dicky Imanuel Jeppy (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2020)
Information is data that has been processed into a form that has meaning for the recipient and is useful for current or future decision making. Information services that available at the University of Atma Jaya Makassar (UAJM) through the website created by the university. However, there is a problem that occurs that is the slow notification of information. Information disseminated by the university and faculty through the website is rarely accessed by students. In addition to the problems in channeling information from lecturers to students also become an problem such as the distribution of information about the assignments and the absence of lecturer. For this reason, creating an information service system that can help giving out the information quickly from lecturers and staff to students is needed. This information service system was created using the waterfall method to overcome the problem of late distribution of information to students. The waterfall method is one of the System Development Life Cycle (SDLC) model which suggest a systematic approach and the process flows from one stage to another. The results of this study are an email based information service system where information services that have been made can facilitate students to obtain information both academic and non academic.